ANALISIS KORELASI INVESTMENT OPPORTUNITY SET (IOS) DENGAN KEBIJAKAN DEVIDEN SERTA PERUSAHAAN TUMBUH DAN TIDAK TUMBUH TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) - Saputra, Indra Jaya; Jatiningrum, Citrawati (Jurnal Manajemen dan Keuangan, 2010)
This research aims to give an empirical evidence about the correlation between Investment Opportunity Set (IOS) with deviden payout and deviden yields between growth company and not growth company in Indonesia Stock Exchange (BEI). Data used in this research is obtained from Effect Exchange of Indonesia The Data of Capital Market of FE UGM. Analysis methods is the quantitative analysis by using correlation method used SPSS Ver.15 and by using paired sample t test to give evidence the different between Investment Oportunity Set (IOS) at growth and not growth company.In this research is writer test its hypothesis use theprobability by Î± is 0,05.The result in this research are :First, the correlation between Investment Opportunity Set (IOS) with deviden payout not significantly in statistic (0,150 > 0,05). means that was have not correlation Second, Investment Opportunity Set (IOS) with deviden yield not significantly in statistic (0,103 > 0,05). means that was have not correlation. Third, Investment Opportunity Set between growth and not growth company was not different significantly in statistic both in deviden payout and dviden yieldKeyword : Investment Opportunity Set (IOS), Deviden payout, Deviden Yields